A discrete vortex model for the calculation of aerodynamic loads on a blade of a N-bladed helicopter rotor in rectilinear flight - Arnold, Jacob (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1992.